Chiral Diuranyl(VI) Complexes and Their Catecholase Activities: Experimental and Theoretical Insights. Issue 14 (7th April 2022) - Ghosh, Sabari; Srivastava, Ankit K.; Sharma, Manju; Pal, Samudranil
Abstract: Two enantiomeric pairs of complexes, [(UO2 )2 ( R/S ‐L 1 )2 (H2 O)2 ] ⋅ 2MeCN and [(UO2 )2 ( R/S ‐L 2 )2 (Me2 NCHO)2 ] (H2 R/S ‐L 1 = R/S ‐ N ‐(salicylidene)‐2‐amino‐1‐propanol and H2 R/S ‐L 2 = R/S ‐ N ‐(2‐hydroxy‐1‐naphthylidene)‐2‐amino‐1‐propanol) and their characterization by elemental analysis, mass spectrometry, various spectroscopy and X‐ray crystallography are reported. In each complex, trans ‐UO2 2+ units are in edge‐shared NO4 pentagonal planes formed by the two alkoxide end bridging ONO‐donor ( R/S ‐L 1/2 ) 2− and the two solvent molecules. The first pair is inactive, while the second pair is active towards catecholase activity. The mass spectra suggest formation of the adduct complex−Me2 NCHO+substrate and EPR spectra indicate a radical pathway for the catalytic reaction. Computational studies indicate that primarily the binding strength of the solvent molecule dictates the adduct formation and hence the catalytic inactivity/activity. Based on experimental observations and theoretical calculations a four step mechanism has been proposed for the catalytic activities of the second pair of complexes. Abstract : The enantiomeric pairs of complexes [(UO2 )2 ( R/S ‐L 1 )2 (H2 O)2 ] and [(UO2 )2 ( R/S ‐L 2 )2 (Me2 NCHO)2 ] (H2 R/S ‐L 1 = R/S ‐ N ‐(salicylidene)‐2‐amino‐1‐propanol and H2 R/S ‐L 2 = R/S ‐ N ‐(2‐hydroxy‐1‐naphthylidene)‐2‐amino‐1‐propanol) are reported. Catecholase inactivity of the first pair and activity of the second pair are demonstrated and probed.